The influence of organizational culture and work environment on the performance mediated by job satisfaction at the Ministry of XYZ - Rachmadany, Syawindra Abi Nur; Wanasida, Albert Surya (Institute of Computer Science (IOCS), 2024)
In the era of globalization and demands for transparency, government institutions are required to improve the performance of civil servants to provide better public services. A strong organizational culture and conducive work environment are expected to support increased employee performance through increased job satisfaction. This research aims to analyze the influence of organizational culture and work environment on the performance of civil servants which is mediated by job satisfaction at the Ministry of XYZ. The method used in this research is quantitative using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Data was collected through questionnaires distributed to 132 employees, with a return rate of 81.8% or 108 respondents who filled in. The research results show that organizational culture and work environment positively and significantly influence job satisfaction and employee performance. Job satisfaction, which is a mediating variable, is also able to mediate the relationship between organizational culture and work environment on employee performance. It is hoped that this research can contribute to the development of knowledge in the field of human resource management, especially in the government sector.